2020
DOI: 10.3389/frai.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Using Topic Modeling Methods for Short-Text Data: A Comparative Analysis

Abstract: With the growth of online social network platforms and applications, large amounts of textual user-generated content are created daily in the form of comments, reviews, and short-text messages. As a result, users often find it challenging to discover useful information or more on the topic being discussed from such content. Machine learning and natural language processing algorithms are used to analyze the massive amount of textual social media data available online, including topic modeling techniques that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(168 citation statements)
references
References 48 publications
1
163
0
4
Order By: Relevance
“…However, the studies conducted by Siti Qomariyaha et al in 2019 (26) by using Twitter data as text data were corroborated with our results in this study as they concluded that LDA considers the relationship between documents in the corpus with the best topic coherence than LSA. Also, in comparative studies using different text mining methods as applied to short text data, LDA showed more meaningful extracted topics and obtained good results with topic coherence as an evaluation metric for creating the content of a document collection (6,27) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the studies conducted by Siti Qomariyaha et al in 2019 (26) by using Twitter data as text data were corroborated with our results in this study as they concluded that LDA considers the relationship between documents in the corpus with the best topic coherence than LSA. Also, in comparative studies using different text mining methods as applied to short text data, LDA showed more meaningful extracted topics and obtained good results with topic coherence as an evaluation metric for creating the content of a document collection (6,27) .…”
Section: Discussionmentioning
confidence: 98%
“…Latent Semantic Analysis is a method for representing and extracting the contextual meaning of words through statistical computations over a text corpus (6) , (14,15) . It is formerly known as Latent Semantic Indexing (LSI) (16) , before LSI, Information is fetched by accurately matching words in documents with the queries using lexical matching methods.…”
Section: Latent Semantic Analysis (Lsa)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the algorithm cannot model the relationships between the created topics. LDA is the most popular algorithm which is studied extensively in many domains [21] and reported to work effectively in generating the context for the collection of documents [22]. [23] overviews topic modeling approaches and suggest a guideline for choosing most suitable method for the specific analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, research efforts [9], [17] is limited in this field, and they are based on Latent Dirichlet Allocation (LDA) [13], which does not perform well in short texts because of their sparseness. Recently, many TM-based short texts (e.g., tweets, or Facebook status) categorisation approaches [15], [16], [19]- [23], have proposed novel methods to improve the performance of topic-based categorisers in short texts. These proposals can be useful in IoT service descriptions categorisation as they are generally short and sparse.…”
Section: Introductionmentioning
confidence: 99%